Impact of justice and solidarity variables on the acceptability of managed realignment. (3rd April 2017) - Rulleau, Bénédicte; Rey-Valette, Hélène; Clément, Valérie
Abstract : Sea-level rise due to climate change will have significant effects on coastal areas and populations. Adaptation policies recommend the managed realignment of the most vulnerable assets and activities. Despite their medium- and long-term benefits, these policies face significant friction due to social acceptability in the communities where they are implemented. This article investigates the hypothesis that respecting principles of justice in the implementation of managed realignment should increase its acceptability. We compare preferences of those people who are exposed to the risk of climate-change-induced flooding and those who are not, as regards funding managed retreat policies and defining compensation criteria for assets at risk. The main theories of social justice provide the four principles included in the analysis: efficiency, need, responsibility and priority assigned to property rights. A choice experiment survey was conducted with 258 residents of coastal and hinterland communities in the south of France. Four attributes were selected to define the managed realignment policy: the dialogue arrangements, the implementation period, the policy implementation schedule and the cost. The results show support for a relatively fast launch of these policies (within 15 years) but in stages and through a process of dialogue with the population. People's perceptions of the funding criteria reveal a preference for national solidarity. Finally, national funding of managed retreat policies and compensation criteria based on market prices have a significant positive influence on the acceptability of managed realignment policies, whereas introducing responsibility-based compensation criteria tends to favour the status quo over the adaptation policy. Policy relevance Prioritization of the funding criteria reveals the preference for national solidarity. Preferences for the justice criteria underpinning compensation reveal a great diversity of values. Besides implantation modalities, preferences for managed realignment policies depend on which level they are implemented at, on the expropriation criteria (the emphasis given to property rights, i.e. market price), on the attachment (people perceived as worst off, i.e. the property is their main residence rather than a second home or they have lower levels of income) and on the degree of responsibility (related to the date of purchase, i.e. on the information given at the time on the risk).